PENGARUH PENYELESAIAN PIUTANG MASYARAKAT TERHADAP OPTIMALISASI PENGELOLAAN DANA PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) - Nuryadin, Rusmin; Sampara, Nirwana; Bachtiar, Yusran (Universitas Muhammadiyah Parepare, 2018)
This research aims to analyze and know accurately on the influence of the settlement accounts receivable of society towards the optimization of the management of Rural Agribusiness Enterprise Development Fund (PUAP) case study Gapoktan Sub Tiroang Pinrang Regency Of South Sulawesi. The data used in this research is the primary data obtained from principals of agriculture in farmers groups, and also the employees in Department of agriculture and Peternakansertapegawai in the Tiroang subdistrict of South Sulawesi Regency Pinrang through secondary data questionnaires and instruments in this research will be measured using the Likert scale. The method used is the linear regression analysis of the sederhanabertujuanmenganalisisdan know akuratPengaruhPenyelesaian Receivable Communities against the optimization of the management of funds, rural Agribusiness Enterprise Development abbreviated PUAP case study Gapoktan Sub Tiroang Regency Pinrang South Sulawesi. The results showed that the free variables in terms of the settlement accounts receivable of society do not affect significantly to variables bound PUAP fund management. In addition to the management of the Fund PUAP influenced by Settlement accounts receivable of communities affected by variables outside of the research which is not specified explicitly. From the results of the analysis of the influence of the settlement accounts receivable of society against the management of the Fund by the method of simple linear PUAP inconclusive diintrepretasikan that variable Settlement accounts receivable of society against the management of the Fund not PUAP significantly influential in other words (H0 is accepted (Ha) was rejected.